Dpal kye rdo rje źes bya ba'i rgyud kyi rgyal po'i 'grel pa legs bśad ñi ma'i 'od zer źes bya ba bźugs so: the detailed commentary on the great Hevajra Tantra - Bkra-shis-rnam-rgyal (Drikung Kagyu Publications)
Commentary on Hevajratantra